Study of social and geographical factors affecting the spread of COVID-19 in Ethiopia. Issue 1 (2nd January 2021) - Kumar, Rajesh; Pandey, Amit; Ibsa, Rabira Geleta; Sinwar, Deepak; Dhaka, Vijaypal Singh
Abstract: Corona VIrus Disease 2019 (COVID-19) caused by 2019 novel Coronavirus (2019-nCoV) becomes the global pandemic that has affected the economy of almost every country in the world. Out of 5.6 million cases as on May 26, 2020 it has already consumed around 0.34 million lives. As compared to first case of 2019-nCoV in Wuhan City, China in December 2019, the very first case in Ethiopia was notified on March 12, 2020 and till May 26, 2020 the number of people infected with this disease becomes 655. There are numerous social and geographical factors that are responsible for spreading of the deadly virus. This paper has presented a study of these social and geographical factors, specifically in Ethiopia. To validate the study, several statistical techniques are used to analyze the effect of these factors in calculating transmission rate in Ethiopia. The study shows that the age, gender, immunity, nutritional deficiencies, and deprived household problems are directly correlated with the spread of COVID-19 in Ethiopia.